Redescription and extended geographical distribution of Peltaea chiquitana (Malvaceae, Malvoideae) - José Fernandes-Júnior,Aluisio (2020)
Abstract Peltaea chiquitana has been a name of dubious identity due to the incomplete original description and original materials lacking fruits. Recent herbaria and field work studies have uncovered new data for this species. Thus, we present a redescription of P. chiquitana, including, for the first time, details of column, fruit, and seed morphology. An extended geographical distribution of P. chiquitana is presented, based on the first records of the species to Brazil. Furthermore, line drawings, scanning electronic microscope photographs, a distribution map, and a conservation assessment are presented here.